2023
DOI: 10.20428/jss.v29i3.2180
|View full text |Cite
|
Sign up to set email alerts
|

Arabic and English Relative Clauses and Machine Translation Challenges

Khalil A. Nagi

Abstract: The study aims at performing an error analysis as well as providing an evaluation of the quality of neural machine translation (NMT) represented by Google Translate when translating relative clauses. The study uses two test suites are composed of sentences that contain relative clauses. The first test suite composes of 108 pair sentences that are translated from English to Arabic whereas the second composes of 72 Arabic sentences that are translated into English. Errors annotation is performed by 6 professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although the difference in the number of studies that researched Arabic-English MT compared to studies that researched English-Arabic translation is not highly significant, the results signal the need for conducting more studies that investigate MT in relation to Arabic-English. While some studies concluded that error frequency in Arabic-English translation is less than that in English-Arabic translation [57,58] stressed the need for postediting to improve MT adequacy and fluency in Arabic-English translation. The following chart provides a visual representation of results in terms of language-pair direction.…”
Section: Data Extraction Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the difference in the number of studies that researched Arabic-English MT compared to studies that researched English-Arabic translation is not highly significant, the results signal the need for conducting more studies that investigate MT in relation to Arabic-English. While some studies concluded that error frequency in Arabic-English translation is less than that in English-Arabic translation [57,58] stressed the need for postediting to improve MT adequacy and fluency in Arabic-English translation. The following chart provides a visual representation of results in terms of language-pair direction.…”
Section: Data Extraction Synthesis and Analysismentioning
confidence: 99%
“…Evaluative studies stressed the significance of translation evaluation to improve the performance of Arabic MT engines and suggest strategies to overcome relevant shortcomings [55,61,65]. Considering the limited research on Arabic MT effectiveness in dealing with specialized content [100], some studies addressed MT shortcomings in translating specialized texts or textual components such as the legal discourse [100], literary features [66], proverbs [67], sentiment words [101], relative clauses [57], as well as social media vernacular [102]. Evaluative studies continued to dominate the literature on MT systems to highlight their affordances and limitations in terms of adequacy, accuracy, fluency, context sensitivity, terminology and other criteria and called for complementarity between MT and HT via pre-editing and postediting [50,53,58,63,70,103].…”
Section: Between 2020-2023mentioning
confidence: 99%